Verification of durability of novel applications - Bragança, L. (2006)
Durability of structural concrete can be assessed according to standards, when the degradation models of materials and their combinations as well as experiences from the use are available in a reliable way. In the case of innovative structural materials and applications, the needs to verify durability may lead to extensive studies on the application of current methods. A state-of-the-art of durability verification of functional concrete materials and steel-concrete composite structures shows that existing knowledge is in common adaptable but needs interpretation and systematic identification of risks. However, there are several sources of uncertainty in the methods themselves like e.g. the influence of loading. Further, interaction between different materials inside a structure is in some examples an additional source of chemical reactions and degradation, but the service life design methods typically rely on environmental classes.